Genetic analysis of yield and quality traits through generation mean analysis in rice - Sreelakshmi, Ch; Ramesh Babu, P (ORYZA-An International Journal of Rice, 2019)
The present investigation in rice (Oryza sativa L.) was undertaken to study the magnitude of gene action in two cross combinations for eleven yield and twelve quality traits deploying generation mean analysis following six parameter model for parents (P1 and P2), F1, F2, BC1 and BC2 generations during three crop seasons. The results of the scaling tests revealed that the additive-dominance model was inadequate for all of the characters evaluated in both the crosses suggested the existence of epistasis in the inheritance of these characters. Mean values of both the crosses revealed significant for most of the traits except effective bearing tillers per plant, SCMR, harvest index, kernel length and kernel L/B ratio in the cross BPT 5204 x IR 64. Major contribution of duplicateepistasis was revealed by the two crosses, for most of the characters. Few traits revealed complementary epistasis in both the crosses. The present study demonstrates the importance of additive, dominance and epistatic geneeffects for the inheritance of almost all the yield as well as quality characters studied.